Role of light desinchronosis in the development of metabolic disorders in wistar rats of the breed in experiment - Е. G. Zarubina; I. A. Gribanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
An experimental simulation of light desynchronosis was carried out on 60 rats of male Wistar breed at the age of 6 months, weighing 280–300 g to study its effect on carbohydrate and fat metabolism. It was found that prolonged exposure to rats under conditions of light deprivation leads to pronounced metabolic disturbances leading to the formation of hypercholesterolemia and hyperglycemia in the experimental group of animals.